2004
DOI: 10.1002/eji.200425117
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐apoptotic mechanism and reduced expression of phospholipase D in spontaneous and Fas‐stimulated apoptosis of human neutrophils

Abstract: Neutrophil apoptosis is a constitutive process that can be enhanced or delayed by signals triggered by various stimuli. In this work, we investigated the action mechanism of phospholipase D (PLD) and its expression in the inhibition of spontaneous and Fas-mediated apoptosis. Anti-Fas antibody-stimulated apoptosis of neutrophils was significantly blocked by the exogenous addition of bacterial PLD from Streptomyces chromofuscus (scPLD), and neutrophils cultured for 24 h in the presence of anti-Fas antibody showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Leung et al [19] observed no effect of IL-18, while Brach et al [3] and Klein et al [14] saw no effect of fMLP on neutrophil apoptosis. However, Colotta et al [4], Hu et al [11] and Lee et al [16,17] noted that fMLP inhibits neutrophil apoptosis despite high intracellular concentrations of Ca 2+ ions, which disturb cell potential and induce apoptosis. Inhibition of neutrophil apoptosis by rhIL-18 or fMLP action prolongs the effective action of these cells, which may affect the conditions occurring with excessive amounts of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Leung et al [19] observed no effect of IL-18, while Brach et al [3] and Klein et al [14] saw no effect of fMLP on neutrophil apoptosis. However, Colotta et al [4], Hu et al [11] and Lee et al [16,17] noted that fMLP inhibits neutrophil apoptosis despite high intracellular concentrations of Ca 2+ ions, which disturb cell potential and induce apoptosis. Inhibition of neutrophil apoptosis by rhIL-18 or fMLP action prolongs the effective action of these cells, which may affect the conditions occurring with excessive amounts of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its physiological functions (membrane trafficking), PLD is involved in microbial killing (54), neutrophil degranulation (55), and migration in leukocytes (56). In neutrophils, PLD also has an antiapoptotic role (33). Moreover, activated caspases were shown to reduce the expression and activity of PLD in human neutrophils (33).…”
Section: Fig 3 Tulathromycin Reduces Levels Of Prostaglandin E 2 In Cmentioning
confidence: 99%
“…In neutrophils, PLD also has an antiapoptotic role (33). Moreover, activated caspases were shown to reduce the expression and activity of PLD in human neutrophils (33). In view of our previous observations that tulathromycin was able to promote neutrophil apoptosis (28), we investigated the effect of tulathromycin on PLD activity.…”
Section: Fig 3 Tulathromycin Reduces Levels Of Prostaglandin E 2 In Cmentioning
confidence: 99%
“…These pro-apoptotic compounds increased the rate of apoptosis by up to 90% after 24 h culture (Lee et al, 2004). The CD80, CD83, and CD86 levels were higher in the neutrophils treated with brefeldin A or PDTC than in the neutrophils cultured with media alone (Figure 4).…”
Section: Effect Of Pro-apoptotic Compounds On the Expression Of DC Mamentioning
confidence: 95%
“…The neutrophils rapidly underwent spontaneous apoptosis in the in vitro culture. More than 50-60% of the cells were annexin V-positive and had a typical apoptotic cell morphology after 24 h of culture (Lee et al, 2004). The cells were then double stained for the PE-conjugated DC markers and annexin V-FITC.…”
Section: The Expression Level Of DC Markers On Apoptotic Neutrophilsmentioning
confidence: 99%